2023
DOI: 10.3389/fnetp.2023.1111306
|View full text |Cite
|
Sign up to set email alerts
|

Probing microdomain Ca2+ activity and synaptic transmission with a node-based tripartite synapse model

Abstract: Astrocytic fine processes are the most minor structures of astrocytes but host much of the Ca2+ activity. These localized Ca2+ signals spatially restricted to microdomains are crucial for information processing and synaptic transmission. However, the mechanistic link between astrocytic nanoscale processes and microdomain Ca2+ activity remains hazily understood because of the technical difficulties in accessing this structurally unresolved region. In this study, we used computational models to disentangle the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The CHARMM36m force field was used for the protein, ions other than Ca 2+ , and the lipids [36] . For the Ca 2+ ions, the multi-site model developed by Zhang et al was used, which has recently been shown by us and other groups to reliably model Ca 2+ currents in a range of ion channels [37][38][39][40][41] Hydrogen mass re-partitioning (HMR) of the system was used in the simulations with Na + ions such that 4-fs time steps could be employed [42] . However, 4-fs time steps are incompatible with the multi-site Ca 2+ model, and consequently, a standard 2-fs time step was used in all simulations with Ca 2+ , retaining HMR for consistency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CHARMM36m force field was used for the protein, ions other than Ca 2+ , and the lipids [36] . For the Ca 2+ ions, the multi-site model developed by Zhang et al was used, which has recently been shown by us and other groups to reliably model Ca 2+ currents in a range of ion channels [37][38][39][40][41] Hydrogen mass re-partitioning (HMR) of the system was used in the simulations with Na + ions such that 4-fs time steps could be employed [42] . However, 4-fs time steps are incompatible with the multi-site Ca 2+ model, and consequently, a standard 2-fs time step was used in all simulations with Ca 2+ , retaining HMR for consistency.…”
Section: Methodsmentioning
confidence: 99%
“…The CHARMM36m force field was used for the protein, ions other than Ca 2+ , and the lipids [36] . For the Ca 2+ ions, the multi-site model developed by Zhang et al was used, which has recently been shown by us and other groups to reliably model Ca 2+ currents in a range of ion channels [37–41]…”
Section: Methodsmentioning
confidence: 99%
“…The system appears to be inactive based on the principal variable rates. By initializing both variables to zero, experimental measurements have been made for Ca 2+ and h. To duplicate the model, IP 3 levels have been limited at 0.16µM (that is equal to IP * 3 ) until Ca 2+ and h have been balanced [36][37][38].…”
Section: Endocannabinoid Dynamicsmentioning
confidence: 99%
“…Many of these models are characterised by highly detailed neuron models and glial models of much lower biophysical detail ( Kager et al, 2000 ; Kager et al, 2002 ; Kager et al, 2007 ; Fröhlich et al, 2006 ; Cressman et al, 2009 ; Florence et al, 2009 ; Ullah and Schiff, 2010 ), such that the models can assess qualitative effects of glial potassium buffering but cannot provide insights into how individual glial actors operate during potassium clearance. Recent scientific and technological advances have stimulated the emergence of more complex neuron–glia models (e.g., Sibille et al, 2015 ; Du et al, 2016 ; Depannemaecker et al, 2022 ; Du et al, 2022 ; Liu et al, 2023 ), which are capable of reproducing and predicting quantitatively a wide range of phenomena. However, their complexity makes it challenging to pinpoint which part of the model is responsible for a certain type of behaviour.…”
Section: Introductionmentioning
confidence: 99%